Management of Physiotherapy With Infrared (IR), Electrical Stimulation, and Massage on Bell's Palsy Dextra - Novita Sabila Ramdhani; Suci Amanati (Sean Institute, 2025)
In this study, the case raised was a 17-year-old patient with Bell's Palsy Dextra who experienced complaints in the form of a deviation of the face to the left, weakness of the muscles of the right face, and disturbances when eating and drinking. Based on theory and literature review, the management of physiotherapy in Bell's Palsy includes the use of Infra Red to improve blood circulation and reduce pain, Electrical Stimulation to stimulate facial muscles and nerves, and Massage to improve the strength and function of facial muscles. Method In this research, this is a case study, raising patient cases and collecting data through the physiotherapy process. The modalities provided are Infra Red, Electrical Stimulation, and Massage. Conclusion In this study, the management of physiotherapy with Infra Red, Electrical Stimulation, and Massage for four times of therapy was proven to be effective in increasing facial muscle strength, reducing the level of pressure pain, and improving facial expression function in patients with Bell's Palsy Dextra. These results support that the combination of these three modalities can speed up the rehabilitation process and improve the overall quality of life of patients.